Synthesising (Beyond) Ethnographies— Meta-ethnography Revisited - Višić, Maroje (Etnoantropološki problemi / Issues in Ethnology and Anthropology, 2023)
Meta-ethnography is an interpretive knowledge synthesis used for synthesizing data from ethnographic studies. It compares and analyses metaphors/data, creating a new interpretation or developing a new theory. Meta-ethnography was originally introduced by Noblit and Hare in 1988, and in the past thirty-five years, acquired popularity in different disciplines. But by today’s standards, the seminal text left stages of conducting meta-ethnography insufficiently described in terms of transparency and systematicity and being open to different interpretations. This paper aims to discuss and analyse seven phases of conducting meta-ethnography and to suggest how transparency and systematicity in each phase might be enhanced. The author acknowledges that meta-ethnography is still an evolving method and concludes that suggestions made in this paper may serve meta-ethnographers not as an anchor but as a compass in planning and executing each stage.